Evaluation of the Effect of Diode Laser on Healing after Gingivectomy - Shalabh Mehrotra; Amit Ahuja; Zoya Chowdhary; Kritika S. Adhupia; Aashima Bajaj; Monika Loitongbam (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effect of photobiomodulation of diode laser on the healing of gingiva following gingivectomy. Material and Methods: 15 patients with inflammatory gingival enlargement in the age group 18-65 years were enrolled for the study according to the inclusion and exclusion criteria and were divided into two groups, i.e., control and test, with a total of 30 sites. Gingivectomy was performed with a scalpel, and the test site was irradiated with a diode laser, which was repeated after 7 days, finally, the patients were recalled after 21 days for re-evaluation. Soft tissue parameters were recorded at baseline and 21 days, and visual analog scale was recorded at 7 days. Also, tissue was excised and sent for histological analysis both at baseline and 21 days, and the data was subjected to statistical analysis. Results: A clinically significant improvement was observed in patient response to pain in the test group compared to the control group (p=0.001). There was an observable improvement in tissue color in the soft tissue analysis (p=0.001) and a significant reduction in the inflammatory component in the histological analysis in the test group as compared to the control group (p=0.001). Conclusion: Diode laser has a photobiomodulation effect on wound healing after gingivectomy, thus enhancing the rate of healing and decreasing post-operative pain.